Challenging USB fingerprint scanner security protocol: a methodology using casting agents to capture digit and latent ridge detail to enable access. (2016) - McKenna, Samuel; Butler, Mark
Fingerprint scanners are used as a form of control with access limited to the beholder of the ridge detail. However, to what extent these devices are capable of providing that control has not been fully explored. This study tested the reliability of a fingerprint scanner in accessing enrolled fingerprint data, when faced with the challenge of fake fingerprints. Ridge detail casts were crafted from moulds, with gelatine and silicone being applied as casting agents. The second stage required participants to place fingerprints on a bottle or tile; these latent impressions were subsequently powdered using Magneta Flake. Provil, a forensic casting material was applied directly onto the powder, creating simulated fingerprints from a latent print. Each of the produced fingerprints then went through a scanning process. All materials tested were able to gain access through the participants' enrolled data. This suggests potential unreliability of the fingerprint scanner in storing pertinent data.